The Urgency of Mastering Problem Solving In Islamic Education: a Study of Concepts and Educator Functions - Muhammad Zakki Mubarok; Hayati Binti Ismail; Sakinah Binti Ahmad (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2023)
Problem-solving involves seeking information, analyzing situations, and identifying problems to generate alternatives so can make teacher decisions to achieve goals. This article aims to unravel the urgency of educators in mastering problem-solving in classroom learning. Using a conceptual approach, this qualitative descriptive research concludes that one of the functions of educators is to master one of the problem-solving models. One of the competencies of mastering problem solving is the ability to think critically as a tool in constructing knowledge during the learning process. With problem- solving, educators are able to produce school graduates who are proportional and thrive in the future fairly and equitably.